The effect of three recovery protocols on blood lactate clearance after race-paced swimming - Lomax, M. (The Journal of Strength and Conditioning Research, 2012)
The purpose of the present study was to assess the impact of 3 recovery protocols on blood lactate clearance after maximal intensity swimming. Thirty-three regional standard swimmers were tested throughout the course a year and were required to complete a race-paced 200-m swim in their main stroke or individual medley. After the race-paced swim, swimmers were assigned a self-paced continuous steady rate swim of 20 minutes (self-prescribed); a 20-minute coach-administered modified warm-up consisting of various swimming modes, intensities, and rest intervals (coach prescribed); or a 20-minute land-based recovery consisting of light-intensity walking, skipping, and stretching (land based). Blood lactate concentration was measured from the fingertip before and after the race-paced swim and after the recovery activity. The concentration of blood lactate was higher (p < 0.01) after race-paced swimming (range of 10.5-11.0 mmol/L) compared with baseline (range 1.3-1.4 mmol/L). However, there were no differences (p > 0.05) between the groups (recovery protocols) at these time points. Conversely, differences were observed between groups after the recovery activities (p < 0.01). Specifically, blood lactate concentration was higher after the land-based activity (3.7 ± 1.8 mmol/L) than either the self-prescribed (2.0 ± 1.2 mmolL) or coach-prescribed (1.8 ± 0.9 mmol/L) swimming protocols. The results of the present study suggest that it does not matter whether a self-paced continuous steady rate swimming velocity or a swimming recovery consisting of various strokes, intensities, and rest intervals is adopted as a recovery activity. As both swimming recoveries removed more blood lactate than the land-based recovery, swimmers should therefore be advised to undertake a swimming-based recovery rather than a land-based recovery.